Confesando a los indígenas. Pecado, culpa y aculturación en América colonial - Valenzuela Márquez, Jaime (Revista Española de Antropología Americana, 2007)
The article explores the uses given to the penitence sacrament in the perspective of the cultural change of the Indians. The confessional manuals are analyzed as a strategy aimed to acculturate the moral practices which were considered incorrect. The change is intended trough a discourse that includes the omnipresence of the sin, the need of introspection of the memory, the communication of faults to the priest and the necessary symbolic punishment. A «mirror game» that seeks the change trough the inner guilt of each person.